The meaning of equality, diversity, and inclusion (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. In this track, you'll improve your understanding of equality, diversity, and inclusion. You'll identify areas in which you can improve your ability to engage in these topics and work towards becoming a more accepting and thoughtful version of yourself. Learning Objectives Learn about the meaning of equality, diversity and inclusion Learn some of the ways you can be more inclusive.